A DEMOGRAPHIC FACTORS ASSOCIATED WITH PUBLIC KNOWLEDGE OF STROKE SYMPTOMS AMONG ASIAN POPULATIONS: A NARRATIVE REVIEW - Herayjat, Akbar; Saepudin; Ratna Mafruhah, Okti (Jurnal Farmasi Sains dan Praktis, 2026)
Public knowledge of stroke symptoms plays an important role in early recognition and timely treatment, particularly in the pre-hospital phase. In Asian populations, demographic characteristics may influence the level of awareness, but findings across studies have not always been consistent. This article aimed to review the relationship between demographic factors and knowledge of stroke symptoms through a narrative review of previous studies. Ten cross-sectional studies published between 2020 and 2025 were identified through database searches in PubMed and Google Scholar with predefined inclusion criteria. The included studies involved heterogeneous populations, including community-based samples, older adults, healthcare professionals, and outpatients with recurrent stroke or transient ischemic attack. Overall, the findings showed that education was the most consistent factor associated with better stroke knowledge. In contrast, associations with age, information sources, place of residence and socioeconomic status varied across studies and settings. Recognition of core stroke symptoms, particularly those reflected in the FAST concept, tended to be better than knowledge of less consistently identified symptoms and appropriate response patterns. Several studies also showed persistent gaps in prevention knowledge, symptom recognition and emergency response. These findings suggest that stroke awareness in Asian populations remains heterogeneous. Community-based education and improved access to context-appropriate health information are therefore needed to strengthen public understanding of stroke symptoms and support early recognition and response.